Recent advances in the role of RNA-binding protein, tristetraprolin, in arthritis. Issue 3 (3rd July 2018) - Yamasaki, Satoshi
Abstract: The expression levels of cytokines and chemokines are strictly regulated at transcriptional and post-transcriptional levels. These small proteins are closely related to inflammatory diseases such as rheumatoid arthritis (RA). The purpose of this review is to highlight the potential utilization of tristetraprolin (TTP) as a therapeutic target in treating RA. TTP is the most notable and well-characterized RNA-binding protein that destabilizes mRNA of pro-inflammatory cytokines. TTP is thought to play an important role in RA because its target mRNA includes a lot of inflammatory cytokines such as TNFα. Post-translational modifications, especially phosphorylation, seem to be critical for the anti-inflammatory effects of TTP. Importantly, various mouse models, many of which are consistent with in vitro studies, are now available to elicit a more detailed understanding of the pathogenic role of TTP. The results of these multidisciplinary studies indicate that it is possible to improve inflammation by controlling TTP activity. Through this review, I propose that the use of recently developed mouse models and establishment of clever designs to target TTP will greatly contribute to future drug development to treat RA.